FISSION-TRACK DATING OF A TEPHRA LAYER IN THE ALAT FORMATION OF THE DANDIERO GROUP (DANAKIL DEPRESSION, ERITREA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Attempts to date a biotite separate from a tephra layer recognized near Buia (Danakil Depression, Eritrea) in the liwer part of the Homo remains – bearing Dandiero group (formerly attributed to the Danakil Formation) using the 39Ar/40Ar method failed because of xenocrystic contamination. For this reason it was applied the fission-track method on glass, since no other phases datable with this technique were present. The quality of glass was very poor for fission-track dating, because of the small size of grains. In addition, after polishing only few glass shards showed useful surfaces for track counting and only 25 spontaneous tracks were counted. The determined fission-track age - 0.75 +/- 0.16 Ma - is a rejuvenated age due to the presence of a certain amount of annealing of spontaneous tracks. An attempt to apply the plateau method for correcting this apparent age failed. A corrected age of 1.3 +/- 0.3 Ma was computed using the size-correction method. In spite of its low precision, this fission-track age represents a significant result, since it corroborates the attribution to Jaramillo Subchron of the normal magnetozone near the base of which the tephra is located.